The Implementation of Photosynthesis Learning to Foster Environmental Awareness among Children of Putera Bonang Orphanage Banjarmasin - Gusti Hadiatus Solehah (World Journal of Islamic Learning and Teaching, 2025)
This study examines the implementation of photosynthesis learning as an effort to foster environmental awareness among children of Putera Bonang Orphanage Banjarmasin. The research was conducted using a qualitative descriptive approach, focusing on the process of learning, the changes in children’s attitudes, and their behavioral responses toward the environment. Data were collected through observation, interviews, and documentation to capture the impact of the learning activities. The findings indicate that introducing photosynthesis through interactive and contextual learning methods not only enhanced children’s understanding of the concept but also encouraged them to adopt more positive attitudes, such as caring for plants, maintaining cleanliness, and engaging in environmentally friendly activities. The study concludes that photosynthesis learning can serve as an effective educational tool to cultivate environmental awareness and responsibility among orphanage children, thus contributing to character development based on scientific knowledge and ecological values.